2015
DOI: 10.7589/2014-08-216
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTAL SUSCEPTIBILITY OF WOOD DUCKS (AIX SPONSA) FOR WEST NILE VIRUS

Abstract: ABSTRACT:Detection of West Nile virus (WNV) has been reported in a variety of wild ducks in the US, but little is known about the pathogenesis and outcome of exposure of the disease in these species. Previous experimental studies of WNV in ducks either have challenged a small number of ducks with WNV or have tested domesticated ducks. To determine susceptibility and immune response, we challenged 7-wk-old Wood Ducks (Aix sponsa) with a 1999 American Crow (Corvus brachyrhynchos) isolate of WNV. Wood Ducks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…Moreover, Lowenthal et al (1994) have indicated that although the initiation of development of avian immune system occurs during the embryogenesis, it is not completely developed until weeks after hatch depending on the avian species (up to 14 wks). As well, the temporary susceptibility of young duckling (Hofmeister et al, 2015;Komar et al, 2003 Shirafuji;, gosling (Austin et al, 2004;Komar et al, 2003;Swayne et al, 2001), ostriches (Allwright et al, 1995), and chicks had declined by age and these birds became resistant to WNV infection. Similar to WNV infection in ducks, Ramadori and Armbrust (2001) and Song et al (2014) clearly illustrated the age-related susceptibility to duck hepatitis virus-1 (DHV-1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Lowenthal et al (1994) have indicated that although the initiation of development of avian immune system occurs during the embryogenesis, it is not completely developed until weeks after hatch depending on the avian species (up to 14 wks). As well, the temporary susceptibility of young duckling (Hofmeister et al, 2015;Komar et al, 2003 Shirafuji;, gosling (Austin et al, 2004;Komar et al, 2003;Swayne et al, 2001), ostriches (Allwright et al, 1995), and chicks had declined by age and these birds became resistant to WNV infection. Similar to WNV infection in ducks, Ramadori and Armbrust (2001) and Song et al (2014) clearly illustrated the age-related susceptibility to duck hepatitis virus-1 (DHV-1).…”
Section: Discussionmentioning
confidence: 99%
“…The most susceptible species belong to the Charadriiformes and Passeriformes orders and they develop severe neurological signs and high mortality rates such as the American crow with 100% mortality (Hofmeister et al, 2015;Nemeth et al, 2011). However, in other birds, they express more restrictive symptoms and death is rarely observed (Van der Meulen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have additionally provided evidence of the susceptibility of domestic or captive ducks to WNV [ 3 , 53 , 54 ]. Ducks develop high-titer viremia in blood and are capable of shedding virus orally [ 55 ]. Geese are also susceptible to WNV, especially young geese, and develop a variety of neurological signs, often resulting in a significant number of deaths [ 4 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions in naturally infected birds have been previously reviewed in detail by Gamino and Höfle [95]. This chart has been modified to include the most recent literature as well as pathologic findings in birds experimentally infected with WNV (Table 1) [106][107][108][109][110][111][112][113][114][115][116]. Ocular lesions are seen in raptors (red-tailed hawks, Cooper s hawks, bald eagles, golden eagles, goshawks) and owls (great horned owls, barred owls) and range from lymphoplasmacytic pectenitis and chorioretinal inflammation and scarring to generalized endophthalmitis [110,[116][117][118][119].…”
Section: Birdsmentioning
confidence: 99%